Giorgia Meloni and the Marbella Speech: An analysis of her vision of feminism on Twitter and in her speeches - Donofrio, Andrea; Rubio Moraga, Ángel Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This work focuses on the vision of feminism of Giorgia Meloni, characterized by a pro-life and pro-family discourse, antagonistic to the "gender ideology". To achieve this goal, her thought on this subject is presented in detail, emphasizing especially the speech of Marbella of 2022. Using tools such as Talkwalker, FollowerWonk and Audiense Insights, we analyze the activity of Italian politics in social networks on this subject and the interaction generated by her comments. Finally, also from the data provided by these social analytics tools, we investigate some aspects of her profile related to this topic.